The global partnership for sustainable development - Yongfu Huang; M. G. Quibria (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper examines whether foreign aid, together with other economic, social and environmental factors, contributes to sustainable development. It starts with a theoretical model where sustainable development is modelled as a different kind of growth that protects the environment. Using factor analysis and newly developed estimation methods for a dynamic panel data model with endogenous regressors, the empirical section finds evidence that foreign aid has been a significantly positive influence on sustainable development in aid recipient countries. This effect is very likely to go through channels related to growth and resources as well as a technology channel with respect to energy intensity. This research has important implications for a post-2015 development framework on international collective action with regard to a sustainable future.
Keywords: O10; O44; I00; F35; F60; 330; sustainable development; aid effectiveness; post-2015 development agenda; economic growth; natural resource exploitations; energy intensity; factor-IV; factor-GMM; Nachhaltige Entwicklung; Entwicklungshilfe